Research and progress on ClC-2 - Wang, Hongwei (Mol Med Rep, 2017)
Chloride channel 2 (ClC-2) is one of the nine mammalian members of the ClC family. The present review discusses the molecular properties of ClC-2, including CLCN2, ClC-2 promoter and the structural properties of ClC-2 protein; physiological properties; functional properties, including the regulation of cell volume. The effects of ClC-2 on the digestive, respiratory, circulatory, nervous and optical systems are also discussed, in addition to the mechanisms involved in the regulation of ClC-2. The review then discusses the diseases associated with ClC-2, including degeneration of the retina, Sjögren's syndrome, age-related cataracts, degeneration of the testes, azoospermia, lung cancer, constipation, repair of impaired intestinal mucosa barrier, leukemia, cystic fibrosis, leukoencephalopathy, epilepsy and diabetes mellitus. It was concluded that future investigations of ClC-2 are likely to be focused on developing specific drugs, activators and inhibitors regulating the expression of ClC-2 to treat diseases associated with ClC-2. The determination of CLCN2 is required to prevent and treat several diseases associated with ClC-2.